The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/hyp.8016
|View full text |Cite
|
Sign up to set email alerts
|

Submarine groundwater discharge and seawater circulation in a subterranean estuary beneath a tidal flat

Abstract: Abstract:A numerical simulation and stationary geophysical survey at Omaehama, Japan, described the hydrogeology in a tidal flat and adjacent sea water column. The simulation of a tidally influenced aquifer with inland fresh groundwater discharges showed three circulations in the subterranean tidal flat estuary: a small, tide-induced recirculation (TIR) near the sloping beach, a deeper circulation (DC) across the interface between saltwater and freshwater, and a large, tidal flat-induced circulation (TFIC) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…The tidal stage (ebbing or flooding) may also impact the residence time, as it is well-known that seawater infiltration occurs during high tide and drainage during low tide (Nielsen 1990). Infiltration typically occurs faster than draining, resulting in variable porewater residence time during tidal stages for water to react with sediments and build higher concentrations (Nakada et al 2011). Another explanation of lower-end nutrient concentrations in the groundwater samples may be the influence of pumping of groundwater during our study.…”
Section: Nutrient Fluxesmentioning
confidence: 90%
See 1 more Smart Citation
“…The tidal stage (ebbing or flooding) may also impact the residence time, as it is well-known that seawater infiltration occurs during high tide and drainage during low tide (Nielsen 1990). Infiltration typically occurs faster than draining, resulting in variable porewater residence time during tidal stages for water to react with sediments and build higher concentrations (Nakada et al 2011). Another explanation of lower-end nutrient concentrations in the groundwater samples may be the influence of pumping of groundwater during our study.…”
Section: Nutrient Fluxesmentioning
confidence: 90%
“…At AI, the SGD flux based on Rn was higher compared to the SGD flux based on Ra, suggesting some contribution of freshwater inputs at this site (indeed fresher groundwater was encountered). Conditions such as topographic relief can play an important role in SGD, seawater infiltration, subsurface flow, and the overall impact on transport mechanisms (Nakada et al 2011). Saltwater infiltration can be intensified at the beach face of a low-relief estuary, but infiltration has been shown to be even stronger at tidal flat settings (Mao et al 2006).…”
Section: Sgd Derived From the Nearshore Modelmentioning
confidence: 99%
“…Moore 1996;Li et al 1999). Ignoring seepage face, Nakada et al (2011) reported the seawater circulation in a subterranean estuary beneath a tidal sand flat using SEAWAT-2000. The tidal contribution to SGD was estimated to be ∼20 m 3 d −1 m −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large research effort dedicated to the understanding of the freshwater-groundwater exchange in coastal aquifers (e.g., Li et al, 1999;Michael et al, 2005;Nakada et al, 2011;Qu et al, 2014), studies developed in the past have never addressed the evaluation of possible effects of excavating navigable canals through tidal flats on the underlying hydrogeological system. However, in-depth investigations using direct measurements (isotopes, benthic chambers), geophysical surveys, and modeling simulations revealed that submarine groundwater discharge (SGD) may provide considerable freshwater inputs to coastal waterbodies (e.g., Rapaglia et al, 2010;Wang et al, 2015) and may be the primary pathway for nutrients and other contaminants to enter coastal lagoons (e.g., Rapaglia, 2005;Rocha et al, 2016;Santos et al, 2008;Tait et al, 2013).…”
Section: Introductionmentioning
confidence: 99%